Deucravacitinib Induces Proteasomal Degradation of YAP1 in Human Glioblastoma Cells - Wang, Shaonan; Sun, Min; Su, Yajuan; Xu, Zhou; Li, Ang; He, Weiwei (Synlett)
Deucravacitinib is a selective allosteric inhibitor of tyrosine kinase 2 (TYK2) recently approved by the FDA for the treatment of plaque psoriasis. We discovered that this compound induces proteasomal degradation of YAP1, the downstream effector of the Hippo signaling pathway, in human glioblastoma (GBM) cells (U-87 MG). This degradation is independent of the canonical Hippo pathway, which offers clues to alternative mechanisms for YAP1 regulation.